A simple solar energy harvester for wireless sensor networks - Chien, L.J. (Institute of Electrical and Electronics Engineers Inc., 2017)
Wireless Sensor Network (WSN) is an advanced technology that allows users to monitor the environmental or physical condition such as light intensity, temperature, pressure and many more. Generally, WSN motes are powered by two AA sized batteries. However, these batteries have a limited lifespan and need to be changed whenever their energy supply is depleted. Therefore, solutions using energy harvesting system has been proposed to overcome this problem. Nevertheless, many existing design are quite complicated. In this work, a simple and low cost solar energy harvester for WSN is developed. Solar power was chosen due to its wide availability and high power density. The solar energy harvesting circuit consists of a solar panel, rechargeable batteries and a voltage regulator. Experimental results of the harvester have shown that even a simple solar energy harvesting system is able to supply sufficient energy to ensure the WSN's continuous operation. Furthermore, the simple solar harvester design can provide a starting guide for researchers and engineers to quickly obtain a working knowledge in this exciting and emerging area. © 2016 IEEE.